Descriptive study of apical periodontitis detected in Cone Beam Computed Tomography scans - MORETI,Lucieni Cristina Trovati (2016)
ABSTRACT Objective: To perform a descriptive study in order to evaluate apical periodontitis in endodontically treated teeth using cone beam computed tomography. Methods: Eighty-six exams presenting at least one apical periodontitis were selected and divided into two groups: 1 for the mandible and 2 for the maxilla. All the exams were done using the same cone beam computed tomography with standard acquisition settings. All the images were processed and manipulated using the same software. Then the lesions were classified according to the periapical index, but not considering the expansion and/or destruction of cortical. Results: 127 mandibular teeth and 180 maxillary teeth exhibited apical periodontitis with an average size of 0.49 mm in the mandible and 0.75 mm in the maxilla. It was found that the lower pre-molars were the teeth most affected. Lesions identified with scores between 0 and 1 correspond to 83.47% of the lesions in the mandible and 78.89% in the maxilla, and 55.12% of endodontically treated lower teeth and 50% of upper teeth presented no lesion recurrence or lesions under repair. Conclusion: There was a predominance of small apical periodontitis, the pre-molars being the teeth most affected.